If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 7) = (6x + 4) Reorder the terms: 6(7 + x) = (6x + 4) (7 * 6 + x * 6) = (6x + 4) (42 + 6x) = (6x + 4) Reorder the terms: 42 + 6x = (4 + 6x) Remove parenthesis around (4 + 6x) 42 + 6x = 4 + 6x Add '-6x' to each side of the equation. 42 + 6x + -6x = 4 + 6x + -6x Combine like terms: 6x + -6x = 0 42 + 0 = 4 + 6x + -6x 42 = 4 + 6x + -6x Combine like terms: 6x + -6x = 0 42 = 4 + 0 42 = 4 Solving 42 = 4 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 3x+15=x+5.5 | | x^3-6x^2+4x-40=0 | | 26logx=-19 | | Log[6](2x-9)=4 | | 1+-4=N | | 7(1-4x)+3x=107 | | y=e^9t+e^8 | | 4g-4-6-4g= | | ln(y)=9t+8 | | 5x+30=2x+27 | | 0.60x+0.20(60)=0.30(94) | | 3(2x+5)-2(x+4)=27 | | -8x+12=3x | | 3h+6=h-10 | | 4c+1=c-5 | | 5y-5=6y | | -3x+6-2=4 | | 8x-4=7-3x+6+16 | | 8h+7=h-7 | | -6x^2-53x+9=0 | | 0.15x^2+0.85x+1=0 | | 8x-5=x+1 | | 9y^2-6y^4+9y^2-4=0 | | -13+(-3)=M | | 7z+10-4z=2+2z-7 | | 0.30x+12=15.6 | | 13+(-3)=b | | 797=(x-4)(y-8) | | 450=3t+4.9t^2 | | 50=3t+4.9t^2 | | X+x(0.08)=100 | | 7+(-3)=m |